Influence of Fiber Hybridization on Strength and Toughness of RC Beams - Mohammed Muneer Meera Sahib; Surumi Rasia Salim (Civil Engineering Journal, 2022)
This paper focuses on the experimental investigation designed to study the behavior of hybrid fiber-reinforced concrete (HFRC) beams under flexure and impact loading. The addition of fibers to concrete can improve a number of its properties. For optimal response, different types of fibers may be suitably combined to produce HFRC. Optimized combinations of different fiber types in concrete can produce a composite with better engineering properties than that with only one type. The study compared the mechanical properties of fresh and hardened HFRC, Steel Fiber Reinforced Concrete (SFRC), and conventional concrete to arrive at the optimum fiber content for improved behavior of concrete by testing 135 specimens. Subsequently, the behavior of steel fiber-reinforced concrete beams was investigated with and without fiber hybridization under flexural and impact loading, followed by a comparison of the results. Fiber hybridization was achieved by developing concrete containing a combination of steel and polypropylene fibers. Eighteen beam specimens of size 1650×200×150 mm were tested in the investigation. Test outcomes demonstrated that the inclusion of fibers in a hybrid form could ensure superior composite performance in terms of flexure and impact resistance when compared to the incorporation of a single type of fibers in reinforced concrete. Doi: 10.28991/CEJ-2022-08-03-010 Full Text: PDF